Saberes de astronomia no 1º e 2º ano do ensino fundamental numa perspectiva de letramento e inclusão - Lima, Maria Luciene de Souza (2006)
This work suggests a discussion about methodologies and didactic-pedagogical activities for the teaching of Astronomy in first and second cycles of the primary school, in a perspective of literacy and inclusion. The presented proposals have been developed in a group of the Public School Alceu Amoroso Lima, North of Natal city, with children since six years old, amongst which two considered as being with special needs . This research aims to demonstrate that it is possible to develop with those children the contents of Astronomy, while they participate of the process of literacy and inclusion. From this, we are searching a theoretical-practical contribution so that the Parâmetros Curriculares Nacionais (Brazilian Nacional Curricular Guideness) include the referred contents in first cycle of primary school. For the accomplishment of this research, Experiential Astronomy was initially proposed. Later on, many workshops had been carried through (clay, ripping , crepon paper, plasticine, cardboard and gastro-lunar ). All the proposed activities were based on the conjunction of contents, which characterized the interdisciplinarity. Through the approach we adopted and the practices we proposed, we could evidence that not only children considered as being normal , but also that ones who carries special needs could appropriate themselves of our writing code, develop and incorporate a daily relationship close to the stuffs of the sky, learn many information about all of this, besides constructing attitudinal, procedural and conceptual contents